UMP shines at the 37th International Exhibition Inventions New Techniques and Products, GENEVA - UMP, PNC (Penerbit UMP, 2009)
UMP researchers scored a I 00% success rate at the recent 37th International Exhibition for Inventions, New Techniques and Products with a total haul of one gold, two silvers and one bronze medal. The five-day event, held in Geneva, Switzerland starting I April 2009 proved to a sweet outing for UMP especially for Dr Hayder A Abdul Bari, who won the sole gold medal as well as a silver medal for his study entitled "Formulation of High Performance, Multipurpose grease using gypsum from Titanium dioxide manufacturing wastes (From Waste to Wealth)" and "A New Technique for Reducing the Pumping Power Losses in Pipelines Carrying High Temperature Liquids Using Minute Quantities of Suspended Solids" respectively.